The Genera of Fungi: Fixing the application of type species of generic names - Pedro W. Crous (2018)
© 2014 International Mycological Association. To ensure a stable platform for fungal taxonomy, it is of paramount importance that the genetic application of generic names be based on their DNA sequence data, and wherever possible, not morphology or ecology alone. To facilitate this process, a new database, accessible at www.GeneraofFungi.org (GoF) was established, which wil l allow deposition of metadata linked to holo-, lecto-, neo- or epitype specimens, cultures and DNA sequence data of the type species of genera. Although there are presently more than 18 000 fungal genera described, we aim to initially focus on the subset of names that have been placed on the "Without-prejudice List of Protected Generic Names of Fungi" (see IMA Fungus 4(2): 381-443, 2013). To enable the global mycological community to keep track of typification events and avoid duplication, special MycoBank Typification identfiers (MBT) will be issued upon deposit of metadata in MycoBank. MycoBank is linked to GoF, thus deposited metadata of generic type species will be displayed in GoF (and vice versa), but will also be linked to Index Fungorum (IF) and the curated RefSeq Targeted Loci (RTL) database in GenBank at the National Center for Biotechnology Information (NCBI). This initial paper focuses on eight genera of appendaged coelomycetes, the type species of which are neo- or epitypified here: Bartalinia (Bartalinia robillardoides; Amphisphaeriaceae, Xylariales), Chaetospermum (Chaetospermum chaetosporum, incertae sedis, Sebacinales), Coniella (Coniella fragariae, Schizoparmaceae, Diaporthales), Crinitospora (Crinitospora pulchra, Melanconidaceae, Diaporthales), Eleutheromyces (Eleutheromyces subulatus, Helotiales), Kellermania (Kellermania yuccigena, Planistromataceae, Botryosphaeriales), Mastigosporium (Mastigosporium album, Helotiales), and Mycotribulus (Mycotribulus mirabilis, Agaricales). Authors interested in contributing accounts of individual genera to larger multi-authored papers to be published in IMA Fungus, should contact the associate editors listed below for the major groups of fungi on the List of Protected Generic Names for Fungi.